Evidence of Population Decline in Common Eiders Breeding in Western Greenland - Merkel, Flemming Ravn (ARCTIC, 2004)
In the Arctic, there is great concern for several eider populations, including the northern common eider (Somateria mollissima borealis) breeding in Canada and Greenland. In 1998-2001, extensive ground surveys were conducted on 937 potential nesting islands in West Greenland, covering most of the districts of Ilulissat, Uummannaq, and Upernavik (69°15' N to 74°05' N). On 216 islands within 106 eider colonies, 4097 ±468 active nests were identified. In 15 colonies where comparable and well-documented surveys were conducted approximately 40 years ago, the study shows a population decline of 81% (from 3361 to 624 nests). A rough comparison shows that of 51 eider colonies surveyed in 1920, 1960, or 1965, 71% either were gone or had declined in breeding numbers when resurveyed in 1998-2001. At the colony level, the 1998-2001 surveys revealed large year-to-year variations in nesting numbers. The reason for the overall decline is not clear. However, there is circumstantial evidence that harvest of common eiders in West Greenland is a key factor. The results urgently call for more cautious management of the northern common eider population. On se préoccupe beaucoup dans l'Arctique de plusieurs populations d'eiders, y compris l'eider à duvet (Somateria mollissima borealis) qui se reproduit au Canada et au Groenland. De 1998 à 2001, on a procédé à de vastes relevés au sol sur 937 îles susceptibles d'abriter des nids dans l'ouest du Groenland, une zone qui recouvrait la plupart des districts d'Ilulissat, d'Uummannaq et d'Upernavik (69° 15' de latit. N. à 74° 05' de latit. N.) Sur 216 îles situées à l'intérieur de 106 colonies d'eiders, on a identifié 4097 ± 468 nids actifs. Dans 15 colonies où des relevés comparables et bien documentés ont été effectués il y a 40 ans, l'étude révèle une baisse de la population de 81 % (soit de 3361 à 624 nids). Une première comparaison montre que des 51 colonies d'eiders étudiées en 1920, 1960 ou 1965, 71 % avaient soit disparu, soit enregistré une baisse du nombre de paires lors des ...